1958
DOI: 10.1161/01.res.6.5.612
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Uptake of the Nonworking Left Ventricle

Abstract: Comparisons have been made in the open chest dog of the oxygen usage of the left ventricle whose external work has been reduced to zero by 4 different procedures. The average oxygen usage of the left myocardium/100 Gm./min. is about 2.0 cc. in complete arrest with vagal stimulation or with intracoronary potassium injection; 3.8 cc. in fibrillation; and 3.4 cc. in the empty but beating heart. The oxygen value in the arrested heart approximates 27 per cent of that in the control state and the uptake during vagal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0
1

Year Published

1961
1961
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(30 citation statements)
references
References 19 publications
7
22
0
1
Order By: Relevance
“…However, when pressures are lowered in parallel in all branches of the left coronary artery, there will be global left ventricular ischemia, as well. We do not believe that our findings can be explained by the effects of global myocardial ischemia, because the differences between pressure-flow relations described when interarterial pressure gradients were present and were absent were similar in beating hearts and during diastolic arrest; in the latter, ischemia would be minimal or absent because the metabolic demand during cardiac arrest is only about 20% of that in the beating heart (McKeever et al, 1958;Monroe and French, 1960). There is no doubt that ischemia would have occurred at low flows in the beating heart, but even then it could not explain our results.…”
Section: Effects Of Interarterial Pressure Gradientsmentioning
confidence: 71%
“…However, when pressures are lowered in parallel in all branches of the left coronary artery, there will be global left ventricular ischemia, as well. We do not believe that our findings can be explained by the effects of global myocardial ischemia, because the differences between pressure-flow relations described when interarterial pressure gradients were present and were absent were similar in beating hearts and during diastolic arrest; in the latter, ischemia would be minimal or absent because the metabolic demand during cardiac arrest is only about 20% of that in the beating heart (McKeever et al, 1958;Monroe and French, 1960). There is no doubt that ischemia would have occurred at low flows in the beating heart, but even then it could not explain our results.…”
Section: Effects Of Interarterial Pressure Gradientsmentioning
confidence: 71%
“…The myocardial basal metabolism may be constant even if heart rate is changed, because it has been shown not to be influenced so much even by large dose of catecholamines (Klocke et al 1965). In this experiment, 2 ml/100gHW/min (McKeever et al 1958;Van Citters et al 1957) was subtracted from MVO2/min as oxygen consumption for myocardial basal metabolism. As stated above, left ventricular systolic peak pressure (LVSP) and Vmax were highly significantly correlated with the corrected MVO2, and left ventricular end-diastolic volume (LVEDV) was correlated at a borderline significance.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies in mature dogs have demonstrated that the major determinants of myocardial oxygen consumption in anesthetized mature dogs are contractility and wall stress, that external cardiac work and basal metabolism are quantitatively less important determinants, and that electrical activation accounts for less than 1 % of myocardial oxygen consumption (3,4,27,28,29). Parmley and Tyberg (30) has estimated that contractility and wall stress each account for 30-40% of total myocardial oxygen consumption in the basal state whereas external cardiac work and basal metabolism each may account for 10-20%.…”
Section: Discussionmentioning
confidence: 99%